Spazio, luogo, mappe (con una postilla) - Falchetta, Piero (Philosophy Kitchen - Rivista di filosofia contemporanea, 2015)
This paper intends to provide an epistemological reflection on the problem of the representability of space. The author's core argument is that the aporia of the representation of space is mainly revealed by geographical maps. More precisely, a territory cannot be described exhaustively by a map. Nevertheless, the author argues that the process of hominization starts precisely when human beings attempt to describe their ambient in order to identify dangers and opportunities. From a philosophical viewpoint, such an original aporia of space develops throughout the different perspectives on the concepts of topos and chora.